1986
DOI: 10.7326/0003-4819-104-4-488
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to Hepatitis B Core Antigen as a Paradoxical Marker for Non-A, Non-B Hepatitis Agents in Donated Blood

Abstract: The relationship between the presence of antibody to hepatitis B core antigen (anti-HBc) in donor blood and the development of hepatitis in recipients of that blood was studied in 6293 blood donors and 481 recipients who were followed for 6 to 9 months after transfusion. Of 193 recipients of at least 1 unit of blood positive for anti-HBc, 23 (11.9%) developed non-A, non-B hepatitis compared with 12 (4.2%) of 288 recipients of only anti-HBc-negative blood (p less than 0.001). Donor anti-HBc status was not signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
80
1
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(89 citation statements)
references
References 22 publications
(5 reference statements)
7
80
1
1
Order By: Relevance
“…Before the advent of EIA tests for anti-HCV, surrogate markers such as ALT and anti-HBc were useful in identifying persons likely to transmit non-A, non-B hepatitis (21)(22)(23)(24). Our study confirms the utility of multiple ALT activity measurements in suggesting the presence or absence of HCV RNA.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Before the advent of EIA tests for anti-HCV, surrogate markers such as ALT and anti-HBc were useful in identifying persons likely to transmit non-A, non-B hepatitis (21)(22)(23)(24). Our study confirms the utility of multiple ALT activity measurements in suggesting the presence or absence of HCV RNA.…”
Section: Discussionsupporting
confidence: 73%
“…The two most helpful markers were alanine aminotransferase (ALT) activity and antibody to the hepatitis B virus core antigen (antiHBc) (21)(22)(23)(24). Several studies have shown that there are differences in the frequency of increased ALT activity and positive anti-HBc between blood donors with low and high absorbance values for anti-HCV (4,9,14,17 ).…”
mentioning
confidence: 99%
“…[26][27][28][29] A number of other studies showed cases of HBV transmission after the transfusion of anti-HBc-positive blood. [13][14][15][16] A recent study showed that up to 16% of anti-HBc/antiHBs-positive donors have circulating HBV-DNA unbound to anti-HBs in their sera and thus in a potentially infective form.…”
Section: Discussionmentioning
confidence: 99%
“…Surrogate testing of blood donors for Anti-HBc and serum ALT and the exclusion of blood which is positive, for either of these may reduce the incidence of NANBH by 40 per cent. 13 Chronic hepatitis is a frequent sequel of NANBH occurring after transfusion, with abnormal liver function tests persisting for more than a year in 10 to 60 per cent of patients. 3s…”
Section: Non-a Non-b Hepatitis (Nanbh)mentioning
confidence: 99%